In Silico Study of Potential Active Compounds in Guava Leaves (Psidium guajava L.) Targeting Beta Estrogen for Breast Cancer Therapy - Nazma Mumtaz Sidik; Nabillah Fauziyyah; Nissa Andjani Kusmawidiyanti; Difla 'Afina Ghifari Suhendar; Nawadhir Fauzan; Shela Salsabila; Muchtaridi Muchtaridi (Indonesian Society for Cancer Chemoprevention, 2025)
Breast cancer is a disease that is the main cause of death, especially in women, where malignant cells form in breast tissue. Some breast cancers are sensitive to hormone estrogen. Overexpression that occurs from an estrogen receptor will increase excessive proliferation. ER-β was chosen as a therapeutic target protein because it can inhibit the proliferation and invasion of breast cancer cells and trigger apoptosis. In this in silico study, a test was carried out on the activity of the active compound content of potential secondary metabolites in Guava plants (Psidium guajava L.) in the leaves aimed at the Estrogen Beta receptor (ER-β) for breast cancer therapy. The goal is to obtain new compound candidates to help pharmacological therapy of breast cancer. This can be seen from the results of re-docking of natural ligands (Genistein) and docking of fifty test ligands which are potential secondary metabolite compounds contained in Guava plants (Psidium guajava L.) in the leaves. The compound that has the greatest potential to activate ER-β as an antiproliferation of breast cancer cells is Clionasterol.Keywords: Breast cancer, Psidium guajava L., ER-β Agonist, molecular docking, clionasterol.